2017
DOI: 10.1097/mog.0000000000000344
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid disease

Abstract: Purpose of Review Our objective was to review advances in bile acids (BA) in health and disease published in the last two years. BA diarrhea (BAD) is recognized as a common cause of chronic diarrhea, and its recognition has been facilitated by development of new screening tests. Recent Findings Primary BAD can account for 30% of cases of chronic diarrhea. The mechanisms leading to BAD include inadequate feedback regulation by fibroblast growth factor 19 (FGF-19) from ileal enterocytes, abnormalities in synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…A chronic, watery diarrhea is a common occurrence in patients with bile acid malabsorption (BAM), a condition known to be characterized by significant clinical heterogeneity [1]. BAM is known to worsen the patients’ quality of life and be a challenge for many healthcare services because of direct and indirect costs [2, 3]. Recently, several research groups have focused their interest to altered bile acid (BA) excretion and reabsorption as a prominent cause of chronic diarrhea [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A chronic, watery diarrhea is a common occurrence in patients with bile acid malabsorption (BAM), a condition known to be characterized by significant clinical heterogeneity [1]. BAM is known to worsen the patients’ quality of life and be a challenge for many healthcare services because of direct and indirect costs [2, 3]. Recently, several research groups have focused their interest to altered bile acid (BA) excretion and reabsorption as a prominent cause of chronic diarrhea [2].…”
Section: Introductionmentioning
confidence: 99%
“…BAM is known to worsen the patients’ quality of life and be a challenge for many healthcare services because of direct and indirect costs [2, 3]. Recently, several research groups have focused their interest to altered bile acid (BA) excretion and reabsorption as a prominent cause of chronic diarrhea [2]. Nonetheless, the mechanisms leading to excessive accumulation of BAs are still only partly defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical setting, current main methods to diagnose BAM include the scintigraphic method 75 Sehomotaurocholic acid test ( 75 SeHCAT), the serum levels of 7-α-hydroxy-4-cholesten-3-one (C4) and FGF19, whereas bile acid (BA) excretion can be determined in stools over 48 hours [2] [3]. Studies using SeHCAT have identified four subtypes of BAM generally recognized as: a) ileal disease preventing BA reabsorption, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical setting, current main methods to diagnose BAM include the scintigraphic method 75 Selenium-homotaurocholic acid test ( 75 SeHCAT), the serum levels of 7-α-hydroxy-4-cholesten-3-one (C4) and FGF19, whereas bile acid (BA) excretion can be determined in stools over 48 hours [2] [3].…”
Section: Introductionmentioning
confidence: 99%